Developing an understanding of Year 12 Higher Education decision-making in a Hong Kong International School context - Sharman, Lauren (2015)
Working as a higher education counsellor has led me to consider carefully the needs of students progressing through the senior school and on to their post-high school destinations. Higher education decision-making is complex and multi-faceted. My students, whilst very much rooted in the context of an international school in Hong Kong, sit in a wider spectrum of international higher education consumers, which sees large numbers of young people looking globally for opportunities. Through surveys and interviews with year 12 and 13 students, as well as parents, I have developed a greater understanding of the process that occurs in my context. Unsurprisingly, this journey is riddled with influencers, with parents and country connections holding a great deal of power in the Hong Kong context. There were some surprising insights into developing effective higher education guidance, with students valuing early access to information and clear guidance on how higher education can impact on careers and future prospects. This study has allowed me to better understand the motivations of students in this context with regard to their aspirations, but has also informed my professional practice as a higher education counsellor, to make it more effective for future students.